The Physical and Sensory Properties of Fermented Rice Cake Enriched with the Sea Pineapple Shell Extract. Issue 6 (3rd July 2021) - Wang, Xiao; Liu, Xiaoyong; Kim, Sang Moo
ABSTRACT: The optimal extraction condition of sea pineapple shell extract (SPSE) was obtained using response surface methodology (RSM), in which the SPSE contained total carotenoid content of 25.58 ± 0.30 μg/g dry weight (DW) and total phenolic content of 2.33 ± 0.03 mg/g DW. The hardness, springiness, and cohesiveness of fermented rice cake (FRC) increased when the amount of added SPSE increased, while the specific volume decreased. The color of the surface and section of FRC with SPSE was darker, more reddish, and more yellowish. Compared to the control, the ash, fat, and carbohydrate contents of the FRC with 2.5 g SPSE/kg rice flour slightly increased. Based on sensory evaluation, the FRC with SPSE 2.5 g/kg rice flour was acceptable by consumers. Therefore, the addition of SPSE to FRC is viable as it enhances its nutritional and functional quality, along with novel eating properties.